Implementation of Wordwall Media on Students’ Motivation and Chemistry Learning Outcomes in the Colligative Properties of Solutions Topic - Ikmalia, Helwa; Bahriah, Evi Sapinatul (LAVOISIER: Chemistry Education Journal, 2025)
Student learning motivation in chemistry is often low due to passive and less engaging learning methods, so interactive learning media are needed that can increase engagement and learning outcomes. This study aims to examine the effect of using gamification-based learning media, Wordwall, on student motivation and learning outcomes in the colligative properties of solutions. The study used a quantitative descriptive method with a sample of 35 students of class XII Sainkes 4 SMAN X Bogor Regency. Motivation was measured using a Likert scale questionnaire with six indicators, while learning outcomes were obtained from Mid-Semester Assessment scores and essay assignments. The results showed that the average student learning motivation reached 71% (good category) and the average learning outcome score was 87.2, with female students' motivation and learning outcomes slightly higher than male students, although the difference was not significant. These findings indicate that Wordwall has the potential to increase student engagement and motivation, although the descriptive design of the study does not allow for direct causal conclusions. The practical implication of this study is that the use of Wordwall as an interactive learning strategy can help teachers create more engaging, relevant, and participatory learning experiences in chemistry classes. This research is academically relevant because it highlights the understudied use of gamification-based digital media in the context of chemistry motivation and learning outcomes. The results also open up further research directions with experimental designs, larger samples, and the testing of additional factors such as digital self-efficacy or comparisons of various digital media to strengthen empirical evidence of the influence of interactive media on motivation and learning outcomes.